State Management in React: Redux vs Zustand - A Comprehensive Guide - Veeranjaneyulu Veeri (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article examines the current state of React state management solutions, focusing on Redux and Zustand as primary implementation options. Through empirical data and real-world metrics, the study reveals that while Redux maintains dominance in enterprise applications with 59.6% developer adoption and serves 72% of large-scale applications, Zustand has emerged as a compelling alternative with a 66.7% satisfaction rate, particularly in medium-sized projects. The article covers performance implications, best practices, and potential pitfalls of both solutions, supported by statistical evidence showing that proper state management implementation can reduce render times by up to 42% and improve development velocity by 40%. The article demonstrates that choosing between these solutions significantly impacts project success, with factors such as application scale, team size, and complexity requirements playing crucial roles in the decision-making process.